Accumulation of Heavy Metals in People on a Gluten-Free Diet - Raehsler, Stephanie L.; Choung, Rok Seon; Marietta, Eric V.; Murray, Joseph A. (Clinical gastroenterology and hepatology, 2018)
Specific foods such as fish and rice have high concentrations of metals such as arsenic, mercury, lead, cadmium, and cobalt. Many gluten-free diets (GFDs) include these foods, so we evaluated whether a GFD was associated with increased metal bioaccumulation. We performed a population-based, cross-sectional study using data collected from the National Health and Nutrition Examination Survey (NHANES), from 2009 through 2012, collecting information on the diagnosis of celiac disease and adherence to a GFD. We tested NHANES blood samples to identify individuals with undiagnosed celiac disease, using assays for immunoglobulin A tissue transglutaminase followed by a confirmatory test for endomysial antibody. Among a total of 11,354 NHANES participants, celiac disease was diagnosed in 55 participants, based on test results or a reported clinical diagnosis. We collected NHANES survey data on blood levels of lead, mercury, and cadmium from subjects who were on a GFD (n = 115) and participants who were not on a GFD (n = 11,239). Levels of total arsenic in urine samples were available from 3901 subjects not following a GFD and 32 individuals following a GFD. NHANES participants were asked questions about fish and shellfish consumption. We performed multivariate logistic regression analyses to associate gluten-related conditions with blood concentrations of mercury, cadmium, and lead and urine concentration of total arsenic, adjusting for demographic characteristics, as well as for rice consumption or seafood intake. Geometric means were reported for urinary concentrations of total arsenic and blood concentrations of mercury, cadmium, and lead for demographic groups and subjects with gluten-related conditions (subjects without celiac disease who avoid gluten). Persons following a GFD had significantly increased total blood mercury levels (1.37 mcg/L) compared with persons not on a GFD (0.93 mcg/L) (P = .008), as well as increased blood levels of lead (1.42 vs 1.13 mcg/L; P = .007) and cadmium (0.42 vs 0.34 mcg/L; P = .03). Urine samples from subjects on a GFD had higher concentrations of total arsenic (15.15 mcg/L) than urine samples from subjects not on a GFD (8.38 mcg/L) (P = .002). After controlling for demographic characteristics, levels of all heavy metals remained significantly higher in persons following a GFD, compared with those not following a GFD. After exclusion of persons with celiac disease, people without celiac disease on a GFD (n = 101) had significantly increased blood concentrations of total mercury (1.40 mcg/L) than persons without celiac disease and not on a GFD (n = 10,890) (0.93 mcg/L; P = .02) and higher blood concentrations of lead (1.44 vs 1.13 mcg/L; P = .01) and higher urine concentrations of total arsenic (14.69 mcg/L [n = 3632] vs 8.32 mcg/L [n = 28]; P = .01). Blood samples from persons without celiac disease avoiding gluten had higher levels of cadmium (0.42 mcg/L) than persons without celiac disease and not following a GFD (0.34 mcg/L), but this difference was not significant (P = .06). In an analysis of data collected from NHANES, persons on a GFD had significantly higher urine levels of total arsenic and blood levels of mercury, lead, and cadmium than persons not avoiding gluten. Studies are needed to determine the long-term effects of accumulation of these elements in persons on a GFD.